Tantangan mempertahankan identitas nasional di tengah arus modernisasi - SAPUTRA, WAHYU AGUNG (Maliki Interdisciplinary Journal, 2026)
The rapid development of modern life has created many changes in Indonesian society. Advances in technology, digital communication, and the easy spread of foreign culture have influenced the way people interact, think, and understand national values. These changes provide various benefits in daily activities, yet they also create challenges for maintaining national identity. This paper aims to examine several problems faced by society in preserving Indonesian national identity during the growth of modernization and to describe efforts that can help strengthen national awareness in today’s global era. The study applies a qualitative method through a literature review by collecting information from academic journals, books, scientific articles, and other relevant references related to national identity and social change in Indonesia. The discussion shows that modernization affects public attitudes toward local culture, the use of the Indonesian language, and the understanding of nationalism among younger generations. The influence of digital media and global culture makes foreign lifestyles easier to follow, causing some people to pay less attention to their own cultural heritage. Even so, modernization does not always lead to negative effects. Technology and digital platforms can also become useful tools to introduce Indonesian culture, strengthen character education, and increase love for the nation. Therefore, cooperation between society, educational institutions, and the government is needed so that national identity can remain strong despite continuous social and technological changes.